FAKTOR-FAKTOR YANG MEMPENGARUHI REAL EARNINGS MANAGEMENT - Novita Cendra, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to obtain empirical evidence on the effect of firm size, leverage, board size, board independence, audit comitee, cash flow from operation, and profitability of companies on real earnings management in manufacturing companies of basic industry and chemicals sector listed in Indonesia Stock Exchange in the period 2015-2017. Research samples are 21 companies out of 66 companies data using purposive sampling method. Results of this research obtained the firm size, leverage, and board size have no significant effect to real earnings management, board independence have positive significant effect, audit comitee haveno effect to real earnings management, cash flow from operation and profitability have negative significant effect to real earnings management.